RESELLER AND DROPSHIP ANALYSIS IN ONLINE BUSINESS ACCORDING TO SHARIA ECONOMIC PERSPECTIVE - Maskur Maskur; Budiman budiman (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2022)
ABSTRACTThis research was conducted to obtain information about the mechanism of Online Business with the Dropshipping system by Dropshipper Natura World. The online business concept of this dropshipping system creates a new phenomenon where the seller (dropshipper) does not stock and own/see directly the goods to be traded, the dropshipper also does not deliver the goods, because the supplier of the goods will send the goods to the consumer under the name of the dropshipper as the sender, but consumers do not know this. In that business in Islamic economics is based on the basic principles/values of business ethics in Islam, namely honesty, justice, trustworthiness and so on. This type of research is descriptive qualitative research and the subjects used as sources in this research are Rangkasbitung World Members, Lebak Regency who sell online using a reseller and dropshipper system. Collecting data in this study using observation techniques, interview techniques (interviews), and documentation techniques. The research instruments used were observation instruments, and interview instruments. The results show that the online business mechanism using the reseller and dropshipper system carried out by Natura World members is not to distinguish between dropshippers and resellers, management only relies on the price or pricelist used for dropshippers / resellers. resellers carried out by Natura World members in accordance with the concept of business ethics in Islam where the goods being traded exist and the price of the goods is clear according to the agreement of the seller and buyer.Keywords: Online Business, Dropshipping, Dropshipper, Reseller, Supplier, IslamicEconom